Visual images in men's magazines and the social and economic construction of masculine identity in China and Singapore. - Khoo, Michele Cheng Hoon. (2010)
In the context of the globalised changes in the social and economic relations between the genders, the present study examined the process and extent through which men internalized the images and messages on masculinity that they received from the media and their socio-cultural environment. The present study has helped to explicate the complex internal adaptation process and the subsequent manifestation of masculinity that the men would deftly execute as they navigate the course of their lives. It was a significant contribution to the current corpus of studies on gender identity as by rendering masculinity problematic, it brought to the foreground, the existing power relations between the genders and challenged the prevailing assumptions about masculinity. Based on the case study approach, China and Singapore were selected as the study sites after careful consideration of scope for comparison, logistical costs, and ease data collection. Data were collected and analyzed through content analysis, survey, and focus group interviews. The content analysis was carried out on 24 issues (2004 to 2007) of For Him Magazine (FHM) in both countries. The focus group interviews were carried out with six groups of men from the two countries and the survey was administered to 800 men in the two countries.